2009
DOI: 10.4020/jhrs.25.4
|View full text |Cite
|
Sign up to set email alerts
|

The Resurfacing of Bepridil Hydrochloride on the World Stage as an Antiarrhythmic Drug for Atrial Fibrillation

Abstract: Bepridil hydrochloride is a multiple ion channel blocker with relatively strong suppressive effects for various K þ channels. Recent clinical studies mainly done in Japan have revealed the efficacy of the agent for the management of atrial fibrillation (AF). The pharmacological conversion effect for persistent AF seems particularly promising. The agent also has robust effects in maintaining sinus rhythm after pharmacological or electrical conversion, as well as suppressing recurrent attacks of paroxysmal AF. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Due to its cardiovascular side effects, specifically TdP, Bepridil was discontinued in the United States. However, Bepridil is still widely used in other countries 34 . Despite the side effects induced by daily, systemic, and high concentrations of Bepridil, we believe that short-term use may result in fewer adverse effects and may be less problematic than that observed in angina patients requiring long-term treatment (>4 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its cardiovascular side effects, specifically TdP, Bepridil was discontinued in the United States. However, Bepridil is still widely used in other countries 34 . Despite the side effects induced by daily, systemic, and high concentrations of Bepridil, we believe that short-term use may result in fewer adverse effects and may be less problematic than that observed in angina patients requiring long-term treatment (>4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the side effects induced by daily, systemic, and high concentrations of Bepridil, we believe that short-term use may result in fewer adverse effects and may be less problematic than that observed in angina patients requiring long-term treatment (>4 weeks). Most of the patients that developed TdP had received relatively high doses of Bepridil 35 , whereas more recent clinical reviews on patients with atrial fibrillation that received Bepridil treatment, propose not to exceed a dose of maximum 200 mg/ day 34 . The risk-to-benefit value to the patient of short-term use of Bepridil would of course require careful consideration and would have to be implemented with caution to account for the potential side effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is classified as a class IV antiarrhythmic drug, prescribed for the treatment of angina pectoris and supraventricular and ventricular arrhythmia. 42,43 Our results show that the NOTCH1 pathway was inhibited at concentrations of bepridil that induced apoptosis in CLL cells. Furthermore, despite the risk of a QTc-prolongation (and more rarely torsades de pointes), at NOTCH1 inhibitory concentrations, bepridil can be safely administered in a hospital setting to people.…”
Section: Discussionmentioning
confidence: 62%
“…Available in France and Japan, bepridil is an FDA‐approved non‐selective ion channels blocker. It is classified as a class IV antiarrhythmic drug, prescribed for the treatment of angina pectoris and supraventricular and ventricular arrhythmia . Our results show that the NOTCH1 pathway was inhibited at concentrations of bepridil that induced apoptosis in CLL cells.…”
Section: Discussionmentioning
confidence: 66%
“…Japanese insurance coverage for persistent AF is limited for amiodarone in heart failure or hypertrophic cardiomyopathy, or for bepridil. Because there are some reports of QT prolongation and torsade de pointes during bepridil therapy for AF with organic heart disease, 583 bepridil is not described as first‐line therapy, but amiodarone and sotalol are listed with comments about limited insurance coverage (Figure 18). Regarding the use of amiodarone for AF with heart failure, the CHF‐STAT study demonstrated the effect for defibrillation and sinus rhythm maintenance 584 .…”
Section: Atrial Fibrillationmentioning
confidence: 99%